A systematic review of mediation analysis frameworks in studies examining the determinants of cardiometabolic outcomes in people living with HIV - Peter Vanes Ebasone; Nasheeta Peer; Anastase Dzudie; Merveille Foaleng; Johney Melpsa; Andre Pascal Kengne (BMC Medical Research Methodology)
Abstract Introduction Mediation analysis provides a more flexible mechanistic view of the causal relationship between HIV-related factors and cardiometabolic diseases. However, there is limited evidence on how mediation analysis is implemented in this specific research area. We aimed to describe the frameworks used in mediation analysis and examine how these analyses are conducted and reported in studies focusing on cardiometabolic outcomes among people living with HIV (PLWH). Methods Following the PRISMA 2020 Guidelines, we comprehensively searched Medline, CINAHL, Africa-Wide Information and SCOPUS to identify observational studies that employed mediation analysis before October 2023. Two reviewers independently screened studies for eligibility. One reviewer performed data extraction, and two others reviewed the extracted information. Results Nine studies met the inclusion criteria, predominantly focusing on the mediation effects of weight and obesity-related factors on the relationship between HIV serostatus, ART, and cardiometabolic outcomes. The review revealed a diverse application of both traditional and causal mediation frameworks. However, inconsistencies and gaps in reporting were noted, particularly in handling missing data, detailing identifiability assumptions, and the use of sensitivity analyses. Conclusion While some studies of cardiometabolic risks among PLWH have embraced causal mediation frameworks, their overall application remains limited. In addition, we identified notable inconsistencies and gaps in reporting practices. To advance the field, researchers should not only integrate more rigorous causal mediation methods but also closely follow established reporting guidelines, such as the AGReMA Statement, to ensure greater transparency, reliability, and impact of future research.